Analisis Penerapan Perencanaan Pajak PPh Pasal 21 Wajib Orang Pribadi Di PT. Sukses Anugrah Sejahtera - Tia Novira Sucipto (ARBITRASE: Journal of Economics and Accounting, 2022)
The company as an income tax withholder at the end of each takwin year, is required to recalculate, deposit and report the tax payable for employees for the past year. If the determination of the calculation and reporting of taxes relating to employee salaries and wages is incorrect, then the calculation of income tax article 21 is not in accordance with applicable laws and regulations and can cause overpayment / underpayment of income tax payable, this study aims to determine and analyze the application of tax planning PPh article 21 individual taxpayers at PT. Sukses Anugrah Sejahtera.Sampling used is all employees at PT. Sukses Anugrah Sejahtera which amounted to 22 permanent employees. The analysis method used is descriptive. Based on the results of the study, it shows that PT. Sukses Anugrah Sejahtera (SAS) has not calculated and withheld income tax on its employees in accordance with the applicable tax law. It is recommended that further research if you want to follow up on PPH article 21 tax planning in order to further increase the scope of the research. The management is expected to take care of the NPWP for employees who do not yet have an NPWP in accordance with the laws and regulations.